Frequency Dependent Permittivity of Soil and Bentonite: For Lightning Protection and High Frequency Earthing Systems - Sabry R.Z.; Gomes A.; Gomes C.; Kadir M.Z.A.A.; Misron N.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bentonite; Electric network parameters; Lightning; Lightning protection; Permittivity; Backfill material; Dry sand; Earthing system; Electrical parameter; Frequency dependent permittivity; High frequency HF; Lightning protection systems; Electric grounding